Prevalence of Vestibular Disorders in Independent People Over 50 That Experience Dizziness - Figtree, William V. C.; Menant, Jasmine C.; Chau, Allan T.; Hübner, Patrick P.; Lord, Stephen R.; Migliaccio, Americo A. (Frontiers in Neurology, 2021)
People aged over 50 are the most likely to present to a physician for dizziness. It is important to identify the main cause of dizziness in order to develop the best treatment approach. Our goal was to determine the prevalence of benign paroxysmal positional vertigo (BPPV), peripheral, and central vestibular function in people that had experienced dizziness within the past year aged over 50. One hundred and ninety three community-dwelling participants aged 51 to 92 (68 ± 8.7 years; 117 females) were tested using the clinical and video head impulse test (cHIT and vHIT) to test high-frequency vestibular organ function; head thrust dynamic visual acuity (htDVA) test to test high-frequency visual-stability; dizziness handicap inventory (DHI) to measure the impact of dizziness; as well as sinusoidal and unidirectional rotational chair testing to test low- to mid-frequency peripheral and central vestibular function. From these assessments we computed the following measures: HIT gain; htDVA score; DHI score; sinusoidal (whole-body; 0.1 - 2 Hz with 30 deg/s peak-velocity) vestibulo-ocular reflex (VOR) gain and phase; transient (whole-body, 150 deg/s/s acceleration to 50 deg/s constant velocity) VOR gain and time constant; optokinetic nystagmus (OKN) gain and time constant (whole-body, 50o/s constant velocity rotation). Our study showed that BPPV, peripheral or central vestibular hypofunction were present in 34% of participants, suggesting a vestibular cause to their dizziness. Over half (57%) of these with likely vestibular cause had BPPV, which is more than twice the percentage reported in other dizzy clinic studies. Our findings suggest that physical DHI score and VOR time constant were best at detecting those with non-BPPV vestibular loss, but should always be used in conjunction with cHIT or vHIT, and that htDVA score and vHIT gain were best at detecting differences between ipsilesional and contralesional sides.